A Pollen Coat–Inducible Autoinhibited Ca2+-ATPase Expressed in Stigmatic Papilla Cells Is Required for Compatible Pollination in the Brassicaceae. Issue 2 (25th February 2014) - Iwano, Megumi; Igarashi, Motoko; Tarutani, Yoshiaki; Kaothien-Nakayama, Pulla; Nakayama, Hideki; Moriyama, Hideki; Yakabe, Ryo; Entani, Tetsuyuki; Shimosato-Asano, Hiroko; Ueki, Masao; Tamiya, Gen; Takayama, Seiji
Abstract : In the Brassicaceae, the pollen coat of compatible pollen grains contains signaling factors that induce Ca 2+ export from the stigmatic papilla cells. This Ca 2+ export is performed by at least one Ca 2+ pump, ACA13, and is required for pollen germination and successful pollination. Abstract: In the Brassicaceae, intraspecific non-self pollen (compatible pollen) can germinate and grow into stigmatic papilla cells, while self-pollen or interspecific pollen is rejected at this stage. However, the mechanisms underlying this selective acceptance of compatible pollen remain unclear. Here, using a cell-impermeant calcium indicator, we showed that the compatible pollen coat contains signaling molecules that stimulate Ca 2+ export from the papilla cells. Transcriptome analyses of stigmas suggested that autoinhibited Ca 2+ -ATPase13 ( ACA13 ) was induced after both compatible pollination and compatible pollen coat treatment. A complementation test using a yeast Saccharomyces cerevisiae strain lacking major Ca 2+ transport systems suggested that ACA13 indeed functions as an autoinhibited Ca 2+ transporter. ACA13 transcription increased in papilla cells and in transmitting tracts after pollination. ACA13 protein localized to the plasma membrane and to vesicles near the Golgi body and accumulated at the pollen tube penetration site after pollination. The stigma of a T-DNA insertion line of ACA13 exhibited reduced Ca 2+ export, as well as defects in compatible pollen germination and seed production. These findings suggest that stigmatic ACA13 functions in the export of Ca 2+ to the compatible pollen tube, which promotes successful fertilization.